2023
DOI: 10.1177/10870547231155438
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Childhood Attention-Deficit/Hyperactivity Disorder (ADHD) on Children’s Health-Related Quality of Life: A Systematic Review and Meta-Analysis

Abstract: Objective: To investigate the association between children’s health-related quality of life (HRQoL) and childhood attention-deficit/hyperactivity disorder (ADHD). Method: Databases were systematically searched for peer-reviewed literature published between 2010 and 2022. Two reviewers independently screened and assessed the quality of included studies. Meta-analysis was conducted for studies that used the Pediatric Quality of Life Inventory (PedsQL). Results: Twenty-three studies were included, with most rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Studies have shown that children with ADHD at a group level experience lower psychosocial QoL compared to their neurotypical peers without ADHD (Danckaerts et al, 2010; Lee et al, 2016; Wanni Arachchige Dona et al, 2023). The findings of the present study suggest that these differences are quantitative rather than qualitative in nature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that children with ADHD at a group level experience lower psychosocial QoL compared to their neurotypical peers without ADHD (Danckaerts et al, 2010; Lee et al, 2016; Wanni Arachchige Dona et al, 2023). The findings of the present study suggest that these differences are quantitative rather than qualitative in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Other strengths were the inclusion of a large and representative general population sample of 1,967 schoolchildren (see Arildskov, Virring, et al, 2022 for details regarding representativeness) and the inclusion of validated rating scales (Niclasen et al, 2012; Szomlaiski et al, 2009; Varni et al, 2001, 2006). Although we included a generic measure of psychosocial QoL—the PedsQL—this measure is widely applied in studies of ADHD (Lee et al, 2016; Wanni Arachchige Dona et al, 2023), and is considered a reliable and valid school population health measure (Varni et al, 2006). There are also limitations of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the value of non-pharmacological interventions (e.g., parenting interventions, Cognitive Behavior Therapy [CBT], and social skills) has been emphasized (National Institute for Health and Care Excellence, 2018). Children who receive treatment, both medication and non-pharmacological, have better QoL, self-esteem, and academic results than children not receiving treatment (Arnold et al, 2020;Dona et al, 2023;Harpin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%